The Development of Human-Robot Collaborative Assembly Line Model by Considering Availability of Robots, Tools, and Setup Time - Anas Maruf; Cahyadi Nugraha; Amenda Septiala Tarigan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
This research develops a design model of a human-robot collaboration assembly line by taking into account the number of robots, tools, and setup time. The objective function of the proposed mixed integer linear programming model is to minimize cycle time. The results of model testing utilizing various scenarios reveal that the number of available robots, tools, and setup time can all have an impact on the assignment of assembly tasks at workstations. In other words, the suggested model takes into account the practical constraints of human-robot collaboration assembly line design. Further research will be conducted to build efficient algorithms for identifying solutions that take into account the assembly line in companies with a significant number of assembly tasks.